Analysis of the impact of handling and culture on the expansion and functionality of NK cells - Martin-Iglesias, Sara; Herrera, Lara; Santos, Silvia; Vesga, Miguel Ángel; Eguizabal, Cristina; Lanceros-Mendez, Senentxu; Silvan, Unai (Frontiers in Immunology, 2023)
Natural killer (NK) cells are lymphocytes of the innate immune system that play a key role in the elimination of tumor and virus-infected cells. Unlike T cells, NK cell activation is governed by their direct interaction with target cells via the inhibitory and activating receptors present on their cytoplasmic membrane. The simplicity of this activation mechanism has allowed the development of immunotherapies based on the transduction of NK cells with CAR (chimeric antigen receptor) constructs for the treatment of cancer. Despite the advantages of CAR-NK therapy over CAR-T, including their inability to cause graft-versus-host disease in allogenic therapies, a deeper understanding of the impact of their handling is needed in order to increase their functionality and applicability. With that in mind, the present work critically examines the steps required for NK cell isolation, expansion and storage, and analyze the response of the NK cells to these manipulations. The results show that magnetic-assisted cell sorting, traditionally used for NK isolation, increases the CD16+ population of NK cultures only if the protocol includes both, antibody incubation and passage through the isolation column. Furthermore, based on the importance of surface potential on cellular responses, the influence of surfaces with different net surface charge on NK cells has been evaluated, showing that NK cells displayed higher proliferation rates on charged surfaces than on non-charged ones. The present work highlights the relevance of NK cells manipulation for improving the applicability and effectiveness of NK cell-based therapies.